Classroom Management as a Pedagogy of Character: Integrating Pancasila Values in Indonesian Civic Education - Isurmin Isurmin; Connie Connie; Muhammad Kristiawan (Journal of Social Work and Science Education, 2026)
While classroom management is often perceived as a disciplinary mechanism, its potential as a deliberate pedagogy for values internalization remains under-explored, particularly in non-Western educational contexts such as Indonesia. This study examines how classroom management practices implemented by Civic Education (PPKn) teachers function as a pedagogical instrument for fostering Pancasila character among senior high school students. Employing a qualitative instrumental case study design at SMA Negeri 9 Kota Bengkulu, data were gathered through 36 hours of systematic classroom observation across 24 lessons, three in-depth teacher interviews, two student focus group discussions, and document analysis of lesson plans, policy documents, and behavioral logs. Preliminary field data revealed that unexplained student absences averaged 7.6%, and democratic classroom practices remained inconsistently implemented indicating a persistent gap between national character education policy and classroom reality. Data analysis followed the interactive model of Miles, Huberman, and Saldaña with trustworthiness established through methodological triangulation and member checking. Findings reveal that teachers employ a tripartite framework planning, implementation, and evaluation through which Pancasila values are deliberately embedded in classroom structures and routines. During planning, teachers integrate character objectives into lesson design and collaboratively establish classroom norms. During implementation, role modeling, democratic facilitation, cooperative learning, and positive reinforcement create a participatory learning environment. Evaluation employs attitude rubrics, peer and self-assessment, and behavioral documentation to support continuous character growth. Together, these dimensions cultivate five Pancasila character outcomes: religiosity, nationalism, unity, deliberation, and social justice. The study reconceptualizes classroom management as a core pedagogical strategy for citizenship education in culturally specific contexts.